THE STUDENTS INTEREST TOWARDS THE USE OF NATURAL APPROACH IN TEACHING SPEAKING - Masruddin Masruddin (Institut Agama Islam Negeri Palopo, 2013)
This research focusing how is the students interests toward the use of Natural Approach. The objective of the research was to find out the students interest toward the use of natural approach in teaching speaking. And scope of the research to explain the students interest toward the use of natural approach through road map in teaching speaking. that focused on giving and explain direction. The researcher used descriptive method. Data was collected by giving questionnaire to the respondent to find out the students interest toward natural approach. The populations of this research were 20 students. In choosing sample, the researcher applied total sampling. The researcher chose class A. The total numbers of sample were 20 students.Based on the findings, show that the students have high interest toward natural approach it prove The percentages in positive statement there were 14 students (70%) were agree. And in negative statement only 8 students (40%) were disagree and disagree. It means the students have positive interest toward the use of natural approach. The factors which make the students interest toward natural approach because did not make students boring and it used authentic material in teaching English particularly speaking. For example brochure, map, visual aid and games it is good method in delivering material